Технологія отримання деяких формазанів, похідних нафталевої кислоти - Фалалєєва, Тетяна Василівна; Дістанов, Віталій Баламірович (НТУ "ХПІ", 2015)
В даній статті розглянуті питання технологія отримання формазанів, похідних нафталевої кислоти. Синтез формазанів, які випромінюють світло, дозволить розширити їх області використання, наприклад, як фотохромних і термохромних матеріалів, а також може привести до отримання стабільних вільних радикалів, що мають люмінесценцію з новими можливостями. Наведена методика синтезу формазанів, що мають у своїй структурі фрагмент з розвиненою хромофорною системою. В даній роботі описано синтез формазанів з похідними на фталевого ангідриду. Розглянуті деякі технологічні рішення отримання формазанів, похідних нафталевої кислоти.

This article describes how to obtain technology formazans, naphthalic acid derivatives. The interest in synthesis and investigations of formazans is caused by their properties and applications. Recently, the more significance is being gained by the application of formazans in medicine science as indicator and markers for cancer cells. Synthesis of formazans emit the light will expand their areas of application, such as photochromic and thermochromic materials, and may enable obtaining luminescent stable free radicals with new properties. The techniques of formazans synthesis that contain in their structure the fragment with branched chromoforic system has been shown. In this study the sysnthesis of formazans with substituted derivatives of phtalic anhydride is described. Certain technological solutions produce formazans, naphthalic acid derivatives. Process has been divided in stages of production of intermediates and final products. In this article the question of final product manufacture has been studied in details. On the basis of the block – scheme the principal technological scheme for production of formazans, derivatives of phtalic acid, has been made and described.
The technology production of some formazans, naphthalic acid derivatives
Keywords: люмінесценція; стабільні радикали; принципова схема; нафталева кислота; luminescence; stable radicals; principal scheme